Enhancing Organizational Learning Performance through the 'KINOSA' Learning Community: A Case Study at a Senior High School in Lebak, Indonesia - Pamungkas, Aan Subhan; Soegiarto, Asep; Japar, Muhammad; Herdiati, Dian (Gagasan Pendidikan Indonesia, 2024)
This study examines the impact of the "KINOSA" learning community on enhancing organizational learning performance at SMAN 1 Banjarsari, located in Banten Province, Indonesia. Utilizing a qualitative case study approach, the research incorporates observations, in-depth interviews with educators and the school principal, and surveys among members of the learning community. The findings highlight the critical role of the "KINOSA" community in improving three key dimensions: student academic performance, teacher collaboration, and the development of pedagogical expertise. Specifically, student academic scores increased by 15%, while the frequency of teacher collaboration rose by 80%, underscoring the effectiveness of the collaborative learning environment fostered by "KINOSA." Additionally, the community-driven professional development programs significantly enhanced teachers' pedagogical skills, with a particular focus on adaptive teaching methods tailored to student needs. These results align with Peter Senge's framework of organizational learning, which emphasizes the importance of continuous, shared learning within dynamic, responsive organizations. The study advocates for the adoption of learning community models like "KINOSA" in other schools facing similar challenges to holistically improve organizational learning outcomes.